Effects of D128N Mutation on OsSERK2 in Xa21-Mediated Immune Complex: An In Silico Study - Raghib Ishraq Alvy; M. H. M. Mubassir; Mohd Firdaus Abdul-Wahab; Salehhuddin Hamdan (Advances in Agriculture)
Receptor-like kinases (RLKs) are plant proteins that form signaling circuits to transduce information through the plant cell membrane to the nucleus and activate processes that direct growth, development, stress response, and disease resistance. Upon sensing various environmental stress stimuli, RLKs interact with specific targets and recruit several other proteins to initiate the defense mechanism. Among many RLK subfamilies, leucine-rich repeat RLKs (LRR-RLKs) are the largest. Xa21, a member of LRR-RLK, is a vital receptor protein in rice plants that binds with bacterial RaxX21-sY, whereas OsSERK2 is a somatic embryogenic receptor kinase (SERK) that acts as a coreceptor in this process. This study focuses on the effect of a substitution mutation of aspartate128 with asparagine128 (D128N) in OsSERK2 on the interdependent binding pattern of the Xa21, RaxX21-sY, and OsSERK2 D128N proteins. The in silico results showed that the D128N mutation in OsSERK2 can significantly change the interaction pattern of the critical residues of the OsSERK2 and affects its receptor-ligand (Xa21-RaxX21-sY) interaction in the complex. These findings are expected to significantly contribute to the study of the structural basis of Xa21-mediated immunity and the first layer of plant defense mechanisms, thereby aiding further research on these structures and their phenotypic implications.